TSG101, a tumor susceptibility gene, bidirectionally modulates cell invasion through regulating MMP-9 mRNA expression - Sai, Xu Bin (BMC Cancer, 2015)
BACKGROUND: Tumor susceptibility gene 101 (TSG101) was initially identified in fibroblasts as a tumor suppressor gene but subsequent studies show that TSG101 also functions as a tumor-enhancing gene in some epithelial tumor cells. Although previous studies have unraveled diverse biological functions of TSG101, the precise mechanism by which TSG101 is involved in carcinogenesis and tumor progression in a bidirectional and multifaceted manner remains unclear. METHODS: To reveal the mechanism underlying bidirectional modulation of cell invasion by TSG101, we used RNA interference to examine whether TSG101 depletion bidirectionally modulated matrix metalloproteinase (MMP)-9 expression in different cell types. RESULTS: TSG101 depletion promoted cell invasion of HT1080 cells but contrarily reduced cell invasion of HeLaS3 cells. In HT1080 cells, TSG101 depletion increased both baseline and phorbol 12-myristate 13-acetate (PMA)-induced MMP-9 secretion through enhancing MMP-9 mRNA expression, but did not affect the expression or activation of MMP-2. In contrast, TSG101 depletion decreased PMA-induced MMP-9 secretion through reducing MMP-9 mRNA expression in HeLaS3 cells. TSG101 depletion had little impact on the signaling pathways required for the activation of transcription of MMP-9 or MMP-9 mRNA stability in either cell line. CONCLUSION: TSG101 bidirectionally modulates cell invasion through regulating MMP-9 mRNA expression in different cell types. Our results provide a mechanistic context for the role of TSG101 in cell invasion as a multifaceted gene. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-015-1942-1) contains supplementary material, which is available to authorized users.